Targeted killing of rhabdomyosarcoma cells by a MAP-based human cytolytic fusion protein. Issue 2 (1st September 2015) - Brehm, Hannes; Hristodorov, Dmitrij; Pardo, Alessa; Mladenov, Radoslav; Niesen, Judith; Fischer, Rainer; Tur, Mehmet K.; Barth, Stefan
Highlights: New, fully human cytolytic fusion protein based on a microtubule-associated protein (MAP) targeting fetal acetylcholine receptor by scFv35. scFv35-MAP specifically bound to and was rapidly internalized in RMS cells. scFv35-MAP was able to kill RMS cells by apoptosis. We are the first to show the efficacy of a fully hCFP on RMS cells. Additionally we show the efficacy of MAP on another tumor entity. Abstract: The treatment of rhabdomyosarcoma (RMS) is challenging, and the prognosis remains especially poor for high-grade RMS with metastasis. The conventional treatment of RMS is based on multi-agent chemotherapy combined with resection and radiotherapy, which are often marked by low success rate. Alternative therapeutic options include the combination of standard treatments with immunotherapy. We generated a microtubule-associated protein (MAP)-based fully human cytolytic fusion protein (hCFP) targeting the fetal acetylcholine receptor, which is expressed on RMS cells. We were able to express and purify functional scFv35-MAP from Escherichia coli cells . Moreover, we found that scFv35-MAP is rapidly internalized by target cells after binding its receptor, and exhibits specific cytotoxicity toward FL-OH1 and RD cells in vitro . We also confirmed that scFv35-MAP induces apoptosis in FL-OH1 and RD cells. The in vivo potential of scFv35-MAP will need to be considered in further studies.